2014
DOI: 10.2478/hukin-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Short Time Concentric Versus Eccentric Training Program on Electromyography Activity and Peak Torque of Quadriceps

Abstract: The purpose of this study was to examine the effect of an 8-week concentric (CON) versus eccentric (ECC) isokinetic training program on the electromyography (EMG) signal amplitude of vastus medialis (VM), vastus lateralis (VL) and rectus femoris (RF). Also, the isometric (ISO) and dynamic maximum strength of the knee extensors were assessed. Eighteen physically healthy male subjects (age 22 ± 1 years, body height 177 ± 4 cm, body mass 73 ± 7 kg) performed four weeks of unilateral CON isokinetic training for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
1
0
0
2
Order By: Relevance
“…The nonsignificant increase in the concentric torque of the three groups at both angular velocities was consistent with the mode-specificity concept of training that was reported by Carvalho et al, 42 who reported that eccentric training of a short duration induces a greater mode-specific stimulus for an increase in strength because it augments eccentric strength more than the concentric training effect on concentric strength. Moreover, muscle strength gains after concentric and eccentric training rely greatly on the muscle action used for both training and testing.…”
Section: Discussionsupporting
confidence: 90%
“…The nonsignificant increase in the concentric torque of the three groups at both angular velocities was consistent with the mode-specificity concept of training that was reported by Carvalho et al, 42 who reported that eccentric training of a short duration induces a greater mode-specific stimulus for an increase in strength because it augments eccentric strength more than the concentric training effect on concentric strength. Moreover, muscle strength gains after concentric and eccentric training rely greatly on the muscle action used for both training and testing.…”
Section: Discussionsupporting
confidence: 90%
“…De esta forma, en varios estudios se ha utilizado la amplitud de la señal de electromiografía para la valoración de los músculos después de un entrenamiento de fuerza (A. Carvalho, Caserotti, C. Carvalho, Abade y Sampaio, 2014;Liossis, Forsyth, Liossis y Tsolakis, 2013;). El proceso que siguen para determinar el valor de la amplitud de la señal es el siguiente:…”
Section: David Chorro Hernándezunclassified
“…Los futbolistas profesionales tienen un patrón de coactivación intramuscular específico tanto en cuádriceps como en isquiotibiales, al igual que un patrón intermuscular I:C hallado con EMG en ejercicios funcionales de fuerza sin utilizar pruebas de normalización adyacentes. Respecto al primer grupo muscular, el patrón corresponde al encontrado por otros autores que sí utilizaron la EMG junto a la CVIM(Alkner et al, 2000;Carvalho et al, 2014; Para terminar de aclarar este punto, un músculo, por ejemplo el VL, puede tener un RMS en una prueba máxima de 50 RMS y en un ejercicio funcional de 25 RMS. Dicho músculo estaría activándose en el ejercicio funcional al 50% de la prueba máxima.…”
unclassified